El factor cooperación en las organizaciones de economía popular y solidaria. Una aproximación desde las organizaciones de la comuna Ponce Quilotoa. - Cadena Ortiz, Juan Pablo (2020)
The present investigation corresponds to the study realized to the popular and solidarity economy organizations of the Ponce Quilotoa commune. Taking as objective to define strategies that allow the improvement of the cooperation factor as an integrating part of the productive factors that are proposed for this type of organizations. For this study is used a qualitative investigation whose design was non-experimental since none of variables were manipulated to achieve the stated objectives; this was limited to the collection of information directly from the primary source, as well as observation and interviews for further analysis. The most notable results allow identifying that the cooperation factor is present by spontaneously way in the daily work of the diversity productive activities carried out in organizations. However, with the proposal of designing a model for development of solidarity economic circuits organizations from the Ponce Quilotoa commune. It allows strengthening the progress of an alternative economy for the organization of popular and solidary economy, where the corporation factor will be participant in the union of forces a wills, to improve productive capacities and quality of life of the inhabitants in harmony with their natural environment.